PROFIL LOGAM BERAT Cd, Cr (VI) DAN Pb PADA LOKASI BERBEDA DI PROVINSI LAMPUNG SERTA BIOAKUMULASINYA PADA TANAMAN PANGAN - Widowati, Hening; Sari, Kartika; Sulistiani, Widya Sartika (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The heavy metal profile analysis of Cd, Cr(VI) and Pb in the different location in Lampung Province and their bioaccumulation to crops has been conducted. The aims were finding out the difference of metal accumulation in the different pollutant area and determining how it happened to the vegetables surrounding, which were kangkoong and spinach. The research methods were purposive sampling in the different location in Lampung Province, namely 1) highlands, 2) paddy fields, 3) road sides and 4)industrial areas. Based on the results, it is found that the highest metal concentration of Cd, Cr(VI) and Pb are in the industrial area. Commonly, the value of BCFo-w (0,12-2,00) is higher than BCFÂ¬o-s (0,01-0,18) which shows that there is low metal accumulation of Cd, Cr(VI) and Pb in kangkoong and spinach. Furthermore, the BCF value of Cd and Cr(VI) are higher compared to Pb.Â Keywords: Logam berat, Cd, Cr(VI), Pb,bioakumulasi.